Strategies for Handling Stunting: A Case Study in Kediri District - Bayu, Kharisma; Wardhana, Adhitya; Nirwan Wihatmojo, Andarujati; Atriyeni, Devi; Farida, Fifi; Feby Rizky, Thya Mayssy (Efficient: Indonesian Journal of Development Economics, 2024)
The objectives of this research are: (1) identify gaps in stunting prevalence data between the Survey of Nutrition Status Indonesia (SSGI) and Bulan Timbang in Kediri District; (2) identify external and internal factors regarding the handling of stunting in Kediri District. Finally, alternative strategies that are appropriate and can be used as input by policymakers are needed to achieve the target stunting rate with a downward trend from year to year in Kediri District. The research methods used are Gap Analysis, SWOT, and QSPM Matrix. The results showed that the difference in stunting prevalence data in Kediri District in 2022 between Bulan Timbang and the Indonesian Nutrition Status Survey (SSGI) was because SSGI surveyed in Kediri District by random sampling with a total of 710 toddlers, which, according to the Kediri District Health Office, the sampling locations by SSGI were coincidentally the locations with the highest stunting prevalence rates in Kediri District. It is not explained from the 710 toddlers how many toddlers experience stunting.